Hobbes and the law - Dyzenhaus, David; Poole, Thomas (Thomas M.); Cambridge eBooks (Cambridge : Cambridge University Press, 2012)
Hobbes's political thought provokes a perennial fascination. It has become particularly prominent in recent years, with the surge of scholarly interest evidenced by a number of monographs in political theory and philosophy. At the same time, there has been a turn in legal scholarship towards political theory in a way that engages recognisably Hobbesian themes, for example the relationship between security and liberty. However, there is surprisingly little engagement with Hobbes's views on legal theory in general and on certain legal topics, despite the fact that Hobbes devoted whole works to legal inquiry and gave law a prominent role in his works focused on politics. This volume seeks to remedy this gap by providing the first collection of specially commissioned essays devoted to Hobbes and the law.
The political jurisprudence of Thomas Hobbes / Martin Loughlin -- The equal extent of natural and civil law / Ross Harrison -- Thomas Hobbes and the common law / Michael Lobban -- Hobbes on law and prerogative / Thomas Poole -- Criminal law for humans / Alice Ristroph -- Hobbes' relational theory : beneath power and consent / Evan Fox-Decent -- Hobbes on civic liberty and the rule of law / Lars Vinx -- Hobbes on equity / Dennis Klimchuk -- Hobbes on the authority of law / David Dyzenhaus -- Hobbes and the civil law : the use of Roman law in Hobbes's civil science / Daniel Lee.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Hobbes, Thomas, -- 1588-1679.; Law -- Philosophy; Natural law; Electronic books